2017
DOI: 10.1186/s12885-017-3749-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different therapeutic strategies for complete hydatidiform mole in women at least 40 years old: a retrospective cohort study

Abstract: BackgroundThere are three main therapeutic strategies, namely expectant management (dilation and curettage only), prophylactic chemotherapy and prophylactic total hysterectomy for treating older women with complete hydatidiform mole (CHM). However, the scientific community has so far, not unanimously accepted the above-mentioned methods. The objective of this study was to evaluate the effectiveness of these therapeutic strategies in preventing post-molar gestational trophoblastic neoplasia (GTN) pertaining to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
(30 reference statements)
2
11
0
1
Order By: Relevance
“…The participants were at least 40 years old in four studies [14–17], 40 to 49 in one study [13] and 50 or older in one study [12]. All participants were histologically diagnosed with hydatidiform mole consisting of both partial mole and complete mole [14, 16, 17] or only complete hydatidiform mole [12, 13, 15]. The case group included the group of patients who received either hysterectomy [12, 13, 16, 17] or uterine evacuation followed by hysterectomy [14, 15].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The participants were at least 40 years old in four studies [14–17], 40 to 49 in one study [13] and 50 or older in one study [12]. All participants were histologically diagnosed with hydatidiform mole consisting of both partial mole and complete mole [14, 16, 17] or only complete hydatidiform mole [12, 13, 15]. The case group included the group of patients who received either hysterectomy [12, 13, 16, 17] or uterine evacuation followed by hysterectomy [14, 15].…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 22 to 159. The follow-up period were 3–14 years in one study [14] and 3–12 years in another study [15], while for the other four studies [12, 13, 16, 17], such data were not reported. The outcome of each study was predominantly focused on the incidence of post-molar GTN.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, for those women who had dilatation and curettage, GTN developed in 53% and 60% of women aged 40 to 49 years, and ≥50 years respectively [ 22 , 23 ]. Similarly, Zhao et al found that the incidence of post-molar GTN in women aged >40 years was significantly lower in patients who had hysterectomy compared to patients who had dilatation and curettage (11% vs 37%, P =0.004) for complete mole [ 24 ]. In contrast, Giorgione et al reported that in women with hydatidiform mole aged >40 years, primary hysterectomy does not reduce the incidence of port-molar GTN when compared with dilatation and curettage (58% vs 30% respectively, P =0.094) [ 25 ].…”
Section: Surgery For Hydatidiform Molementioning
confidence: 99%